CLIP2 is a potential biomarker for platinum resistance and prognosis in ovarian cancer: a bioinformatics analysis - Qiu, Minghui; Zhao, Mengxing; Zhao, Jiani; Zhao, Haoyun; Jiang, Weiqi; Yang, Lu; Yang, Lindong (Translational Cancer Research, 2026)
Ovarian cancer exhibits the highest mortality rate among gynecologic malignancies. Platinum resistance remains a key determinant of poor clinical outcomes.